Effects of pretreatment with medetomidine, midazolam, ketamine, and their combinations on stress-related hormonal and metabolic responses in isoflurane-anesthetized cats undergoing surgery - Kamohara, Hirokazu; Kamohara, Toshiko; Hikasa, Yoshiaki (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The purpose of this study was to compare the effects of pretreatment with medetomidine (Me), midazolam (Mi), and ketamine (Ke) on stress-related neurohormonal and metabolic responses in isoflurane-anesthetized cats undergoing ovariohysterectomy and castration. Materials and Methods: We prospectively recruited 112 client-owned healthy mixed-breed cats. In both surgeries, we divided the cats into seven groups (eight cats per group): non-treatment (control), Me (50 μg/kg), Mi (0.5 mg/kg), Ke (5 mg/kg), Me + Mi, Me + Ke and Me + Mi + Ke administered intramuscularly. After pretreatments, we maintained anesthesia with isoflurane and oxygen. Venous blood was taken before pretreatment, pre- and post-operatively during anesthesia, and at early- and complete-recovery. Results: Both plasma adrenaline and noradrenaline were reduced during anesthesia in all groups. Plasma cortisol increased during anesthesia and at early recovery in non-Me-treated groups, whereas it decreased in Me-treated groups in both surgeries. Plasma insulin and non-esterified fatty acid (NEFA) decreased, and glucose increased during anesthesia in all groups, but hyperglycemia and decrease in NEFA were greater in Me-treated groups. Conclusions: In isoflurane-anesthetized cats undergoing surgeries, premedication with Me alone and in combination is useful for reducing the perioperative stress-related increase in cortisol and catecholamines except for hyperglycemia. J. Adv. Vet. Anim. Res., 8(4): 563-575, December 2021 http://doi.org/10.5455/javar.2021.h546